Problematic Educational Technology for The Development of Creative Thinking Skills (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This article covers modern methods and methods of their application that encourage creative thinking in teaching geography. Students are presented with facts, reflections on the technology of problematic education on the development of creativism.